Kearifan Lokal Masyarakat Jawa dalam Menghadapi Pandemi - Siti Rumilah; Kholidah Sunni Nafisah; Mochammad Arizamroni; Sholahudin Abinawa Hikam; Sita Arum Damayanti (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2021)
This research discusses various local wisdoms of the Javanese people in dealing with the COVID-19 Pandemic. Plague which means “pagebluk” in Javanese is responded with cultural attitudes such as understanding the wabah (pandemic) in the framework of titen science, jamasan heirloom as a method, and herbal medicine treatment as a method. This research makes use of Social Anthropology theory. The method used is descriptive qualitative. While the research background is Ngawi Regency, East Java. Data were collected from observations and interviews with several sources and literature study. The results of this study show that each region in Indonesia, especially Java, has its own way of responding to the arrival of the COVID-19 outbreak. With existing local wisdom, the Javanese people are trying to deal with this pandemic in their own way and culture.